1996
DOI: 10.2355/isijinternational.36.1453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content on Mechanical Properties of Electroslag Remelted Fe3Al Based Intermetallic Alloys.

Abstract: The effect of carbon content (0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…14) They have demonstrated that the addition of carbon, whether in the form of carbide or graphite, tends to improve the machinability of Fe-Al alloys, but the improvement in machinability is not necessarily followed by increase in tensile ductility. These results are not inconsistent with those of Baligidad et al 7) and Pang and Kumar. 11) The difference is considered to be associated with the different carbon content in the alloys used.…”
Section: Effect Of Carbon Addition On Room Temperature Duc-contrasting
confidence: 39%
See 2 more Smart Citations
“…14) They have demonstrated that the addition of carbon, whether in the form of carbide or graphite, tends to improve the machinability of Fe-Al alloys, but the improvement in machinability is not necessarily followed by increase in tensile ductility. These results are not inconsistent with those of Baligidad et al 7) and Pang and Kumar. 11) The difference is considered to be associated with the different carbon content in the alloys used.…”
Section: Effect Of Carbon Addition On Room Temperature Duc-contrasting
confidence: 39%
“…In view of the fact that carbide-matrix interfaces can serve as hydrogen traps in carbon steels, it is envisaged that the poor room temperature ductility of iron aluminide alloys might be improved by the presence of carbides. In fact, beneficial effect of carbon addition on room temperature ductility of Fe 3 Al and FeAl based alloys has been reported by Baligidad et al 7) and Pang and Kumar, 11) respectively. These workers have suggested that the Fe 3 AlC 0.5 carbides in the grain or at grain boundaries provide interfaces that act as hydrogen traps and delay the embrittlement kinetics.…”
Section: Effect Of Carbon Addition On Room Temperature Duc-mentioning
confidence: 95%
See 1 more Smart Citation
“…High-carbon iron aluminides were not of interest for research, as carbon is known to embrittle these alloys [7]. On the contrary, iron aluminides produced recently by the electroslag remelting process (ESR) were found to improve its strength when carbon is added as an alloying element [8][9][10][11][12]. This is attributed to precipitation hardening by formation of carbides .…”
Section: Introductionmentioning
confidence: 99%
“…To improve their fabrication characteristics, electro-slag remelting of air induction melted cast electrodes was used to produce round ingots free of porosity [9,10]. Efforts are also being made to reduce their environmental embrittlement susceptibility and to improve their ductility [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%